Knowledge of Prenatal Care Nurses toward Management of Toxoplasmosis in Pregnant Women - Khudair, fatima (Iraqi National Journal of Nursing Specialties, 2013)
Objective: This study aims to assess the level of nurse's knowledge regarding toxoplasmosis managementin pregnant women.Methodology: A descriptive analytic study was carried out from January 2012 to March 2012. A sample of(70)nurses who provide prenatal care to pregnant women at primary health care centers of AL-Adala,ALHindia,AL-Askary,AL-Jamea,AL-Ansarand AL-Salam in AL-Najaf city. The questionnaire was self-completedand included questions on sociodemographic characteristics and toxoplasmosis aspects.Results: The findings of the study indicated that (44.3%) of nurses have moderate level of knowledge.(32.9%) of nurses was with age ranging from 31-36 years. (74.3%) were male. (52.9%) were secondarygraduate,(31.4) were institute graduates, regarding the training sessions the majority of nurses(84.3%)have no training sessions, (34.3%) of nurses who were included in the study have duration ofexperience ranging from 7-13 years. Highly significant relation between nurse‘s level of knowledge andtheir age and years of experience (0.009, 0.024) respectivelyRecommendations: The study recommended that: it is necessary to join all nurses who work in prenatalcare units in workshop training, continuing education sessions regarding toxoplasmosis aspects and othermother –child issues to improve health awareness. Another study should be conducted to investigate theassociation between the prevalence of toxoplasmosis and affectivity of prenatal care in preventingtoxoplasmosis.